Investigação da composição química e da capacidade antioxidante dos extratos das folhas de celtis ehrenbergiana - (:unkn) unknown (Universidade Federal do Pampa, 2020)
According to the World Health Organization (WHO), a large part of the world population uses medicinal plants as a primary form of health treatment. Despite the advancement of technology, there are still many unknown species and no scientific reference to support popular use, such as the Celtis ehrenbergiana species. Many species of the genus have medicinal use for oral, internal use, but the studied species presents reports of topical use by the inhabitants of the municipality of Uruguaiana - RS. The aim of the study was to seek information that can contribute to patients undergoing treatment with C. ehrenbergiana leaf tea. The plant material was collected in the city from November 2017 to November 2018 and a phytochemical analysis was previously performed. The lyophilized aqueous extract of Celtis ehrenbergiana (LAECe) was prepared by decoction with distilled water and the crude methanolic extract (MECe) by maceration with methanol. From the ready extracts, the concentrations of total polyphenols were determined, obtaining a content of 41.73 ± 1.67 mg of gallic acid / g for LAECe and 42.36 ± 1.92 mg of gallic acid / g of MECe, 4.64 ± 1.58 mg of quercetin / g of LAECe and 6.63 ± 1.90 mg of quercetin / g of MECe were determined as total flavonoid content, and the de termination of total tannin content was carried out, where 1.12 ± 0.15% was found in LAECe and 0.92 ± 0.10% for MECe. In the MECe analyzed by gas chromatography (GC / MS) nine compounds were identified: vitamin E (28.50%), stigmast-5-en-3-ol oleate (15.57%), 5-hydroxypipecolic acid (14, 63%), gamma-sitosterol (13.52%), trans-squalene (10.39%), n-hexadecanoic acid (8.08%), linolenic acid (3.41%), phytol (3.89% ) and palmitic acid (2.01%), the compounds found had reports of antioxidant activity. The two extracts were analyzed by HPLC-DAD comparing with reference substances for polyphenols and flavonoids, none of the tested compounds were detected in C. ehrenbergiana, but there are reports for the genus on the composition of C-glycosylated flavonoids. In the in vitro antibacterial test, C. ehrenbergiana presented MIC greater than 512 μg / mL and greater than 256 μg / mL for Gram-positive and Gram-negative bacteria, respectively. What does not characterize a considerable biological effect for popular use of species, as the amount of vegetable should be much greater than usual in the preparation of "tea". As a result of inhibiting the capture of free radicals by the DPPH method, LAECe showed greater inhibition than MECe.
Investigation of the chemical composition and antioxidant capacity of extracts from the leaves of celtis ehrenbergiana
Keywords: Celtis ehrenbergiana; CLAE-DAD; Celtis ehrenbergiana; Glycosylated C flavonoids; Ciências farmacêuticas; Pharmaceutical Sciences; CNPQ::CIENCIAS DA SAUDE